2020
DOI: 10.1371/journal.pgen.1008677
|View full text |Cite
|
Sign up to set email alerts
|

A Snf1-related nutrient-responsive kinase antagonizes endocytosis in yeast

Abstract: Endocytosis is regulated in response to changing environmental conditions to adjust plasma membrane (PM) protein composition for optimal cell growth. Protein networks involved in cargo capture and sorting, membrane sculpting and deformation, and vesicle scission have been well-characterized, but less is known about the networks that sense extracellular cues and relay signals to trigger endocytosis of specific cargo. Hal4 and Hal5 are yeast Snf1related kinases that were previously reported to regulate nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 108 publications
0
22
0
Order By: Relevance
“…We found that co-expression of ubiquitin with the kinase Vhs1 resulted in immunodetection of Ser57 phosphorylated ubiquitin ( Figure 3A and Figure 3—figure supplement 1 ). Vhs1 is part of the yeast family of Snf1-related kinases ( Tumolo et al, 2020 ), and additional screening revealed three other kinases in this family that phosphorylated ubiquitin at the Ser57 position: Sks1 (which is 43% identical to Vhs1) ( Figure 3B ), Gin4 and Kcc4 ( Figure 3—figure supplement 2 ). A previous study reported consensus phosphorylation motifs for Vhs1, Gin4, and Kcc4, and all bear similarity to the amino acid sequence surrounding Ser57 in ubiquitin ( Supplementary file 2 ; Mok et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that co-expression of ubiquitin with the kinase Vhs1 resulted in immunodetection of Ser57 phosphorylated ubiquitin ( Figure 3A and Figure 3—figure supplement 1 ). Vhs1 is part of the yeast family of Snf1-related kinases ( Tumolo et al, 2020 ), and additional screening revealed three other kinases in this family that phosphorylated ubiquitin at the Ser57 position: Sks1 (which is 43% identical to Vhs1) ( Figure 3B ), Gin4 and Kcc4 ( Figure 3—figure supplement 2 ). A previous study reported consensus phosphorylation motifs for Vhs1, Gin4, and Kcc4, and all bear similarity to the amino acid sequence surrounding Ser57 in ubiquitin ( Supplementary file 2 ; Mok et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…The family of Snf1-related kinases in yeast share homology with the human AMPK-related kinases ( Tumolo et al, 2020 ). To test if human AMPK-related kinases exhibit activity toward ubiquitin, we performed in vitro kinase assays and found that a subset of this family phosphorylated ubiquitin at the Ser57 position specifically on tetramers ( Figure 3G ).…”
Section: Resultsmentioning
confidence: 99%
“…While both Art1 and Art2 lead to the degradation of AATs, they answer to distinct metabolic cues and are thus wired into distinct signaling pathways. Activation of Art1 by amino acid influx requires the coordinated interplay of TORC1 signaling to inactivate Npr1 (a kinase that negatively regulates Art1) and the action of phosphatases (Gournas et al, 2017, Lee et al, 2019, MacGurn et al, 2011, Tumolo et al, 2020. In response to amino acid limitation, TORC1 is no longer active.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SDC culture medium contains Met (537 μM) which represses Mup1 production. To determine if Myr treatment effects Mup1 in the same way in these two types of media, we examined cells harboring chromosomal MUP1 tagged with ecliptic pHluorin (a GFP variant that loses fluorescence at low pH) which does not fluoresce in the vacuole and late endosomal compartments and thus can be used to quantify the abundance of Mup1 at the PM and early endosomal compartments [68][69][70]. Following transfer of stationary phase cells into fresh SC medium, we observed very low Mup1-pHluorin signal that increased until plateauing at about 4 hr ( Figure 4C).…”
Section: Myriocin Reduces Mup1 Transport Activity In the Plasma Membranementioning
confidence: 99%
“…Mup1 localization and trafficking were analyzed by fluorescence microscopy and flow cytometry as previously described [69,70]…”
Section: Microscopy and Protein Trafficking Assaysmentioning
confidence: 99%